PERAN KOMPETENSI KEPALA SEKOLAH DALAM MEMBANGUN BUDAYA INKLUSIF DI SEKOLAH DASAR - HANAN, ANNIDA LIHASANATI; PUJASMARA, DESTIANA EKA; SOPIAH, ROHAETI NINING; TOSAINI, SALSABILA PUTRI; SYAHIDAH, SHOFIYYAH MUNA; PRIHANTINI, PRIHANTINI (CENDEKIA: Jurnal Ilmu Pengetahuan, 2025)
Education is an important part of shaping the skills and morals of individuals. In doing so, education must create a learning environment that respects the diversity of students and meets the needs of all individuals, including students with special needs. This study examines the role of principals' competencies in building an inclusive culture in primary schools. It aims to explore the relationship between principals' competencies and improving the quality of inclusive education. Using the literature review method, the study analyzed five dimensions of principals' competencies: personality, managerial, entrepreneurial, supervisory and social. The findings show that these competencies play an important role in inclusive policy making, efficient resource management, teachers' professional development and the establishment of harmonious relationships within the school community. The main obstacles faced are the lack of teacher training and limited facilities, which require visionary and collaborative leadership from principals. In conclusion, strengthening principals' competencies is a priority in creating education that is fair, equitable and responsive to the needs of all students ABSTRAKPendidikan merupakan bagian penting dalam membentuk keterampilan dan moral individu. Dalam pelaksanaanya, pendidikan harus menciptakan lingkungan belajar yang menghargai keberagaman siswa dan memenuhi kebutuhan semua individu, termasuk siswa berkebutuhan khusus. Studi ini membahas peran kompetensi kepala sekolah dalam membangun budaya inklusif di sekolah dasar. Penelitian ini bertujuan mengeksplorasi hubungan antara kompetensi kepala sekolah dengan peningkatan kualitas pendidikan inklusif. Dengan menggunakan metode tinjauan literatur, penelitian ini menganalisis lima dimensi kompetensi kepala sekolah: kepribadian, manajerial, kewirausahaan, supervisi, dan sosial. Temuan memperlihatkan bahwa kompetensi ini berperan penting dalam pembuatan kebijakan inklusif, pengelolaan sumber daya yang efisien, pengembangan profesi guru, dan pembentukan hubungan yang harmonis dalam komunitas sekolah. Kendala utama yang dihadapi adalah kurangnya pelatihan guru dan terbatasnya fasilitas, yang membutuhkan kepemimpinan kepala sekolah yang visioner dan kolaboratif. Kesimpulannya, penguatan kompetensi kepala sekolah merupakan prioritas dalam menciptakan pendidikan yang adil, merata, dan responsif terhadap kebutuhan semua siswa.